Photophysical properties of single core multimodal probe for imaging (SCoMPI) in a membrane model and in cells. Issue 7 (11th January 2016) - Hostachy, S.; Swiecicki, J.-M.; Sandt, C.; Delsuc, N.; Policar, C.
Abstract : An unexpected strong luminescence enhancement of a bimodal ReCO probe grafted onto a CPP accurately characterized in a lipid environment. Abstract : The spectroscopic properties of two luminescent Re(i ) tricarbonyl complexes conjugated with two cell-penetrating peptides were examined. Fluorescence experiments and IR quantification in membrane models and in cells showed unexpectedly strong luminescence enhancement for one of the complexes in a lipid environment.